2007
DOI: 10.1007/s11199-007-9219-z
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Objectification: Do Provocative Clothing and Observer Characteristics Matter?

Abstract: This study provides empirical evidence for the objectification of women and unearths factors that increase objectification. Objectification theory (Fredrickson and Roberts 1997) suggests that women from Western cultures are the targets of male gaze. Although this seems selfevident from a look at the media, little empirical evidence exists to document the phenomenon or unravel underlying processes. Undergraduate female participants (N=82) from the Midwestern part of the United States rated three photographs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
107
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(120 citation statements)
references
References 50 publications
9
107
2
2
Order By: Relevance
“…In addition, studies conducted in Belgium (Bernard et al 2012(Bernard et al , 2013(Bernard et al , 2015a and in the U.S.A. showed that female bodies (e.g., wearing swimsuits) are visually perceived as objects. Studies conducted in the U.S.A. (Cikara et al 2010;Gurung and Chrouser 2007), Italy (Vaes et al 2011) and Australia (Loughnan et al 2010) also suggest that sexualized women are perceived by undergraduate students as possessing less intelligence, agency, and humanness (i.e., having thoughts and intentions), and they also elicited less moral concern than fully-clothed women. Despite evidence that sexual objectification entails perceptions of humanness and moral concern, little is known about the practical consequences of sexual objectification.…”
Section: Sexual Objectification and Rape Perceptionmentioning
confidence: 99%
“…In addition, studies conducted in Belgium (Bernard et al 2012(Bernard et al , 2013(Bernard et al , 2015a and in the U.S.A. showed that female bodies (e.g., wearing swimsuits) are visually perceived as objects. Studies conducted in the U.S.A. (Cikara et al 2010;Gurung and Chrouser 2007), Italy (Vaes et al 2011) and Australia (Loughnan et al 2010) also suggest that sexualized women are perceived by undergraduate students as possessing less intelligence, agency, and humanness (i.e., having thoughts and intentions), and they also elicited less moral concern than fully-clothed women. Despite evidence that sexual objectification entails perceptions of humanness and moral concern, little is known about the practical consequences of sexual objectification.…”
Section: Sexual Objectification and Rape Perceptionmentioning
confidence: 99%
“…Clothing is public part of our gender performance that can be judged by others [76,77]. Feminist psychology must remain vigilant and attentive to the fact that powerful sources of gender role restriction and gender typing remain even in a seemingly mundane activity such as Halloween costuming and not to discount their influence despite so many cultural advances for women and girls [38,50].…”
Section: Resultsmentioning
confidence: 99%
“…Undergraduates saw a photo of a young woman who wore revealing or non-revealing clothing. According to objectification theory and subsequent research, the revealing clothing leads to other-objectification (Gurung and Chrouser 2007;Loughnan et al 2013), and the other-objectification (i.e., objectification of the stimulus person) leads to the negative inferences about the woman: that the woman in revealing clothing was likely to provoke the sexual harassment, to have done something to bring about the harassment, and could have prevented the harassment.…”
Section: Discussionmentioning
confidence: 99%
“…Glick et al (2005) found that as compared to a female receptionist, a female manager who emphasized her sexiness evoked less positive emotions, less job competence, and less intelligence. Subsequently, Gurung and Chrouser (2007) found that women wearing sexually stimulating attire were often seen as unintelligent and incapable. Outside the workplace, Vaillancourt and Sharma (2011) utilized evolutionary theory in an experiment wherein young women reacted to a confederate who wore sexy dress or conservative dress.…”
Section: Reactions To Women Wearing Sexy Dressmentioning
confidence: 99%
See 1 more Smart Citation